ANALISIS PENDEKATAN PERILAKU ORGANISASI DALAM KENDALI MUTU DAN KENDALI BIAYA SELAMA PANDEMI COVID-19 DI RS SWASTA X KOTA SEMARANG - Indah Mutiara Puspita Sari; Sutopo Patria Jati; Septo Pawelas Arso (Dian Nuswantoro Semarang, 2023)
ABSTRACTThere was a decrease in quality and cost recovery rate at Private Hospital X Semarang City during the COVID-19 pandemic. Hospitals must implement Quality Control and Cost Control during the COVID-19 pandemic. Hospitals need an understanding of organizational behavior management to optimize Quality Control and Cost Control. Therefore, this study aims to analyze the organizational behavior in quality control and cost control during the COVID-19 pandemic at Private Hospital X Semarang City. This study uses a qualitative method. The organizational behavior analysis by analyzing input, process, and outcomes aspects. Qualitative data collection using in-depth interviews. Informants were determined by purposive sampling. The mains informants consisted of three and three triangulated informants. Data analysis used the method of content analysis (content analysis) by triangulating sources and methods. The results showed that the input aspects were still lacking because they did not have detailed task descriptions understood by the team and had not made guidelines and Standard Operating Procedures (SPO) related to the implementation of quality control and cost control. The process aspects are still lacking because communication is not optimal, leadership has never conducted monitoring evaluations, and team conflicts still occur due to communication and clinical pathway non-compliance. As a result, the outcomes in organizational behavior are still not good, as seen from the lack of cohesion and the function of the quality control and cost control teams who have not carried out scheduled and routine medical audits, and have not carried out utilization.Keywords: The Organizational Behavior, Quality Control, Quality Cost, Hospital, Pandemic COVID-19